Chromosomal mutations in Escherichia coli that improve tolerance to nonvolatile side‐products from dilute acid treatment of sugarcane bagasse. Issue 1 (12th November 2019) - Shi, Aiqin; Yomano, Lorraine P.; York, Sean W.; Zheng, Huabao; Shanmugam, Keelnatham T.; Ingram, Lonnie O.
Abstract: Lignocellulosic biomass provides attractive nonfood carbohydrates for the production of ethanol, and dilute acid pretreatment is a biomass‐independent process for access to these carbohydrates. However, this pretreatment also releases volatile and nonvolatile inhibitors of fermenting microorganisms. To identify unique gene products contributing to sensitivity/tolerance to nonvolatile inhibitors, ethanologenic Escherichia coli strain LY180 was adapted for growth in vacuum‐treated sugarcane bagasse acid hydrolysate (VBHz) lacking furfural and other volatile inhibitors. A mutant, strain AQ15, obtained after approximately 500 generations of growth in VBHz, grew and fermented the sugars in a medium with 50% VBHz. Comparative genome sequence analysis of strains AQ15 and LY180 revealed 95 mutations in strain AQ15. Six of these mutations were also found in strain SL112, an independent inhibitor‐tolerant derivative of strain LY180. Among these six mutations, null mutations in mdh and bacA were identified as contributing factors to VBHz tolerance in strain AQ15, based on the genetic and physiological analysis. The deletion of either gene in strain LY180 increased tolerance to VBHz from approximately 30–50% (vol/vol). Considering the location and physiological role of the two enzymes in the cell, it is likely that the two enzymes contribute to the VBHz sensitivity of ethanologenic E. coli by different mechanisms. Abstract : Increased tolerance of engineered E. coli to biomass acid hydrolysate.